2019
DOI: 10.1002/ptr.6352
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol inhibits non‐small cell lung cancer by repressing expression of NF‐κB‐regulated TRIM59

Abstract: In view of the recognized anti‐tumor properties of eugenol against non‐small cell lung cancer (NSCLC) in cell culture, here we further set out to investigate the potential therapeutic effect of eugenol in vivo and elucidate the underlying molecular mechanism. The relative expression levels of TRIM59 and p65 in NSCLC were quantified by real‐time polymerase chain reaction. Xenograft tumor model was established with TRIM59‐deficient H1975 cells, and tumor progression was monitored. Kaplan–Meier's analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…TRIM59, a member of the TRIM ubiquitin ligase family, has long been considered a tumor marker in association with tumor progression and metastasis in several tumor types, such as non-small cell lung cancer, gastric cancer, osteosarcoma, and cervical cancer [17, 4346]. A recent study reported that depletion of TRIM59 suppresses breast cancer metastasis by promoting RNFT1-induced K63 poly ubiquitination and SQSTM1-directed autophagic degradation of PDCD10 [40].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM59, a member of the TRIM ubiquitin ligase family, has long been considered a tumor marker in association with tumor progression and metastasis in several tumor types, such as non-small cell lung cancer, gastric cancer, osteosarcoma, and cervical cancer [17, 4346]. A recent study reported that depletion of TRIM59 suppresses breast cancer metastasis by promoting RNFT1-induced K63 poly ubiquitination and SQSTM1-directed autophagic degradation of PDCD10 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Clove oil is a clear pale yellowish volatile liquid extracted from Syzygium aromaticum , Myrtaceae, and it is widely used in ambulatory anaesthetization ( Correia et al., 2018 ). Eugenol (C 10 H 12 O 2 ; 2-methoxy-4-2-propenyl), the principal active ingredient in clove oil, is well-known for its antibacterial, antifungal, anti-inflammatory, neuroprotective, and antineoplastic properties ( Cui et al., 2019 ; Garabadu and Sharma, 2019 ; Oroojan, 2020 ; Sakat et al., 2019 ; Tandel et al., 2021 ). In light of that eugenol has acquired a “Generally Recognized as Safe” status from the US Food and Drug Administration, it has extensive applications in pharmaceutical application, health care and cosmetology ( Nisar et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamaldehyde inhibits proliferation, migration, invasion and promotes apoptosis of OS cells and is a potentially valid antitumor agent (Huang et al 2020). 4-Allyl-2-methoxyphenol inhibits non-small cell lung cancer by inhibiting NF-B to regulate TRIM59 expression (Cui et al 2019). Epicatechin gallate can be combined with other compounds to form novel agents that inhibit the tumorigenicity of human papillomavirus-positive head and neck squamous cell carcinomas (Piao et al 2016).…”
Section: Discussionmentioning
confidence: 99%